Microcystins produced by filamentous cyanobacteria in urban lakes. A case study in Mexico City - Pineda-Mendoza, Rosa María; Olvera-Ramírez, Roxana; Martínez-Jerónimo, Fernando (HIDROBIOLÓGICA, 2017)
Cyanobacterial blooms are of great importance because of the toxic effects that these microorganisms are able to induce, particularly on aquatic organisms. Microcystins (MCs) are the principal toxins biosynthesized by cyanobacteria and are powerful inhibitors of the protein phosphatases 1 and 2A. Zooplankton filter feeders such as cladocerans are directly affected by MCs as a result of ingestion of cyanobacteria or contact with intracellular products when cyanobacterial cells break up during and after blooms. A total of 17 strains of filamentous cyanobacteria isolated from three urban lakes in Mexico City were characterized using the microcystin synthetase region mcyA-Cd. Acute 48-h toxicity was evaluated in different strains using the cladoceran Daphnia magna and total microcystin content was determined by enzyme-linked immunosorbent assay (ELISA). The mcyA-Cd region was amplified in 16 microcystin-producing strains; microcystins were detected in eight strains with values ranging from 0.1422 to 2.772 µg L-1. Nevertheless, all aqueous crude extracts induced acute toxicity in D. magna with LC50 values from 363.91 to 741.8 mg L-1 (dry weight). The toxicity observed in non-microcystin-producing strains may be induced by cyclic peptides other than microcystins (anabaenopeptins, microviridins and cyclamides). The results obtained warn of the toxigenic potential of filamentous cyanobacteria, since though Microcystis spp. is frequently predominant in blooms, other toxins and intracellular metabolites released by filamentous cyanobacteria may induce toxicity on aquatic organisms as well as humans.